PENGEMBANGAN MEDIA PLAYDOUGH UNTUK MENINGKATKAN KREATIVITAS ANAK KELOMPOK A - Anita Sri Wulan Sari; Agus Sumitra; Andrisyah Andrisyah (IKIP Siliwangi, 2022)
This background of the research is the low creativity of children, learning activities still use children’s worksheets and write on the blackboard. For this reason, it is necessary to have learning media to increase children’s activity namely using playdough media. The purpose of this study was to develop a playdough media product, see the responses of children and teachers, and find out the increase in children’s creativity after the product was tasted. The method used is research and development (R&D). the research subjects were group A PAD Sakura Cimahi, with eight children. While the data collection techniques use observation, interviews, and documentation. The research was conducted in 8 meetings. The analysis technique uses quantitative descriptive statistics. The results of the research show that 1) the development of playdough media was carried out in a structured manner as planned by the teacher and researcher, then carried out product validation. The results of the validation of material experts and media experts get a percentage of 87,5% and 87,5%. 2) the response of children and teachers to playdough media is very good. 3) the results of increasing children’s creativity showed an increase from 38,25% to 93,35%. In this case, it means that there is an increase of 55,1% for playdough media products that have been tested on children. So it can be concluded that the development of playdough media can increase the creativity of children in group A PAUD Sakura Cimahi.Latar belakang penelitiannya adalah rendahnya kreativitas yang dimiliki anak, dikarenakan kegiatan pembelajaran masih menggunakan lembar kerja anak dan menulis di papan tulis. Untuk itu, perlu adanya media pembelajaran untuk meningkatkan kreativitas anak yaitu menggunakan media playdough. Tujuan penelitian ini adalah mengembangkan produk media playdough, melihat respon anak dan guru, dan mengetahui peningkatan kreativitas anak setelah produk di uji coba. Metode yang digunakanadalahResearch and Development (R&d). Subjek penelitiannya adalah kelompok APAUD Sakura Cimahidengan jumlah delapan anak. Sedangkan teknik pengumpulan data menggunakanobservasi, wawancara dan dokumentasi. Penelitiandilaksanakan sebanyak 8 kali pertemuan.Teknik analisis menggunakan statistika deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa: 1) Pengembangan media playdough dilaksanakan secara tersusun sesuai yang direncanakan oleh guru dan peneliti, selanjutnya melakukan validasi produk. Hasil validasi ahli materi dan ahli media mendapatkan persentase 87,5%, dan 87,5%. 2) Respon anak dan guru terhadap media playdough sangat baik. 3) Hasil peningkatan kreativitas anak menunjukkan terjadi peningkatan yang awalnya mendapatkanpersentase 38,25% meningkat menjadi 93,35%. Dalam hali ini, berarti terjadi peningkatan sebesar 55,1% untuk produk media playdoughyang sudah di uji coba kepada anak.Sehingga dapat disimpulkan bahwa pengembangan media playdough dapat meningkatkan kreativitas anak pada kelompok A PAUD Sakura Cimahi.